2008
DOI: 10.1097/icl.0b013e31818b7428
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Corneal Endothelial Response to Wear of Silicone-Hydrogel Contact Lenses in East Asian Eyes

Abstract: The similarity of bleb responses induced by the silicone-hydrogel lenses under the tested wearing conditions is consistent with the proposition that increases in Dk/t above a certain level will produce minimal change in corneal physiologic conditions compared with that when no lens is worn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In a contralateral study of East Asians, Brennan et al 69 found after 20 min of eye closure, significantly more blebs with low Dk lenses compared with 2 types of silicone hydrogels. In addition, under openeye conditions, two silicone hydrogel lens types produced minimal changes.…”
Section: Endotheliummentioning
confidence: 97%
“…In a contralateral study of East Asians, Brennan et al 69 found after 20 min of eye closure, significantly more blebs with low Dk lenses compared with 2 types of silicone hydrogels. In addition, under openeye conditions, two silicone hydrogel lens types produced minimal changes.…”
Section: Endotheliummentioning
confidence: 97%
“…Brennan et al 11 evaluated the corneal endothelial bleb response to wear of silicone hydrogel lenses (Acuvue Oaysis, Acuvue Advance and Focus Night & Day) and a conventional hydrogel lens (SofLens 38) in eyes of East Asian subjects. SofLens 38 produced a mean percentage area of blebs of 8.0% under closed eye conditions, which was significantly different to that produced by Acuvue Oaysis (1.6%).…”
mentioning
confidence: 99%
“…The magnitude of the response has been found to associate in an inverse fashion, with the oxygen transmissibility of the lens being worn at the time [73][74][75].…”
Section: Morphologymentioning
confidence: 99%